The concepts of psychiatry : a pluralistic approach to the mind and mental illness - Ghaemi, S. Nassir (Johns Hopkins University Press, 2003)
"This book will be of interest to professionals and students in psychiatry as well as psychologists, social workers, philosophers, and general readers who are interested in understanding the field of psychiatry and its pratices at a conceptual level."--Jacket.